Establishing reporting standards for participant characteristics in post-stroke aphasia research: An international e-Delphi exercise and consensus meeting. (February 2023) - Wallace, Sarah J; Isaacs, Megan; Ali, Myzoon; Brady, Marian C
Objective: To establish international, multidisciplinary expert consensus on minimum participant characteristic reporting standards in aphasia research (DESCRIBE project). Methods: An international, three-round e-Delphi exercise and consensus meeting, involving multidisciplinary researchers, clinicians and journal editors working academically or clinically in the field of aphasia. Results: Round 1 of the DESCRIBE e-Delphi exercise ( n  = 156) generated 113 items, 20 of which reached consensus by round 3. The final consensus meeting ( n  = 19 participants) established DESCRIBE's 14 participant characteristics that should be reported in aphasia studies: age; years of education; biological sex; language of treatment/testing; primary language; languages used; history of condition(s) known to impact communication/cognition; history of previous stroke; lesion hemisphere; time since onset of aphasia; conditions arising from the neurological event; and, for communication partner participants, age, biological sex and relationship to person with aphasia. Each characteristic has been defined and matched with standard response options to enable consistent reporting. Conclusion: Aphasia research studies should report the 14 DESCRIBE participant characteristics as a minimum. Consistent adherence to the DESCRIBE minimum reporting standard will reduce research wastage and facilitate evidence-based aphasia management by enabling replication and collation of research findings, and translation of evidence into practice.